ILCA Bulletin No.16. Pastoral systems research - International Livestock Centre for Africa (1983)
Selection of presentations made at the workshop on "Pastoral systems research in sub-Saharan Africa", describing the framework used by ILCA for pastoral systems research (PSR), examining methods used in the descriptive and diagnostic stage of PSR, and showing how the design and testing procedures are followed in practice; with particular reference to low-altitude aerial surveys, livestock surveys & household studies.